CITY LIGHT COMMUNITY CHURCH’S COMMITMENT TO DEVELOPING CAREER READINESS FOR 11TH GRADE STUDENTS AT TERANG NUSANTARA HIGH SCHOOL - Fandy Mulya Latif; Alvin Hartanto; Inggrid Mose; Jimmy Leonardo; Samuel Herman; Yanto Paulus Hermanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Kristen Wira Wacana Sumba, 2025)
This community service program aimed to develop the career readiness of 11th grade students at SMA Terang Nusantara through structured internship and career counseling activities. The program was implemented in June 2025 under the coordination of the CLCC Marketplace Team, involving 23 students and partner companies operating in footwear, property, and paint industries. The applied method integrated community education, training, and consultation approaches, with stages including planning and coordination, socialization, nine day internships, one day career counseling, and evaluation and reflection. The program materials covered practical work in company operational units, work ethics training, and career planning discussions. The results indicated that students gained real work experience, basic skills in relevant fields, and internship certificates that boosted their confidence. Moreover, positive behavioral changes were observed, such as improved time discipline, professional communication, and increased awareness of the importance of career planning. The program also fostered new networks between the school, CLCC, and business partners, which have the potential to become a new institution supporting student career development, and revealed early signs of local leadership initiatives among participants. The conclusion drawn is that collaborative internships involving schools and business partners proved effective in enhancing student career readiness, and it is recommended to expand the program through cross field rotation and continuous cooperation with business partners.